Topseed: Learning Seed Selection Strategies for Symbolic Execution from Scratch - Lee, Jaehyeok; Cha, Sooyoung (Proceedings / International Conference on Software Engineering, 2025)
We present TopSeed, a new approach that automatically selects optimal seeds to enhance symbolic execution. Recently, the performance of symbolic execution has significantly improved through various state-of-the-art techniques, including search strategies and state-pruning heuristics. However, these techniques have typically demonstrated their effectiveness without considering "seeding", which efficiently initializes program states for exploration. This paper aims to select valuable seeds from candidate inputs generated during interactions with any symbolic execution technique, without the need for a predefined seed corpus, thereby maximizing the technique's effectiveness. One major challenge is the vast number of candidates, making it difficult to identify promising seeds. To address this, we introduce a customized online learning algorithm that iteratively groups candidate inputs, ranks each group, and selects a seed from the top-ranked group based on data accumulated during symbolic execution. Experimental results on 17 open-source C programs show that TOPSEED significantly enhances four distinct cuttingedge techniques, implemented on top of two symbolic executors, in terms of branch coverage and bug-finding abilities.